Isolated Limb Perfusion With Melphalan Triggers Immune Activation in Melanoma Patients - Johansson, Junko; Kiffin, Roberta; Andersson, Annica; Lindnér, Per; Naredi, Peter L.; Olofsson Bagge, Roger; Martner, Anna (Frontiers in Oncology, 2018)
Hyperthermic isolated limb perfusion with melphalan (M-ILP) is a treatment option for melanoma patients with metastases confined to the limbs. This study aimed at defining the role of cellular immunity for the clinical response to M-ILP in melanoma patients. It was observed that patients with enhanced cytotoxic CD8+ T cell reactivity to common antigens (HCMV/EBV/influenza virus) prior to M-ILP were more likely to achieve a complete disappearance of macroscopic tumors (complete response). Following M-ILP treatment, the proportions of CD33+CD16+ intermediate and nonclassical monocytes in peripheral blood were significantly enhanced along with induction of HLA-DR on CD4+ and CD8+ T cells. For further studies of the mechanism behind melphalan-induced immune activation an in vitro model, aiming at mimicking the clinical M-ILP protocol, was established, where PBMCs were co-cultured with melanoma cells, which had been pre-exposed to melphalan under mild hyperthermia. Upon exposure to melphalan, melanoma cells showed increased expression of immune-related markers including MHC class I and Hsp70. Moreover, when the melphalan-treated melanoma cells were co-cultured with PBMCs, this triggered an increased proportion of CD33+CD14+CD16++ nonclassical monocytes among the PBMCs. Furthermore, the melphalan-treated melanoma cells stimulated the expansion of CD8+ T cells in the co-cultured PBMCs. These cells produced enhanced levels of IFN-γ and granzyme B and were capable of killing melanoma cells. To further verify an immunogenic role of melphalan, mice were vaccinated with melphalan-exposed murine melanoma cells. When challenged with live melanoma cells, vaccinated mice showed reduced tumor growth and enhanced infiltration of tumor-specific T cells into tumors. We conclude that melphalan-exposed melanoma cells trigger expansion of CD16+ monocytes and activate cytotoxic T cells and that these events may contribute to the antitumoral efficacy of M-ILP.